Late glacial to Holocene deglaciation of the Colle del Vei del Bouc-Colle del Sabbione Area (Argentera Massif, Maritime Alps, Italy-France) - FINSINGER W; RIBOLINI, ADRIANO (2001)
Glacier advances and rock-glacier activity are reconstructed for the Late-Glacial and Holocene periods in the Colle del Sabbione-Colle del Vei del Boue area (French-Italian Alps). Detailed geomorphological mapping and pollen analysis of radiocarbon-dated sediment cores reveal three pre-Little Ice Age glacial phases (S1, S2, and S3) and two rock-glacier generations (R1, R2). Former Equilibrium Line Altitudes (ELA) were obtained using the Balance Ratio method. Micro- and macro-scale features of glacial erosion were used to reconstruct the paleoshape of glaciers and their movement directions. The ELAs of the Vei del Boue and Sabbione glaciers were located respectively 500, 300, and 200 m below Present (about 2800 m a.s.l.). Rock glacier generations are correlated with glacial phases on the basis of their spatial relationships with end moraines. The three glacial phases are related to global climatic oscillations: Oldest Dryas, Younger Dryas, and late Subboreal. During the Younger Dryas, glacier fronts were located at about 2400 m, with the mean ELA at about 2500 m and the Lower Discontinuous Permafrost Boundary (LDPB) at 2300-2400 m. During the Hypsithermal the Vei del Boue and Sabbione glaciers were probably strongly reduced and divided into minor bodies. Timberline rose and Abies likely reached altitudes of 2000 m. Evidence for a pre-LIA maximum Holocene glacial advance is dated to the late Subboreal on the basis of regional vegetation history. A quantitative reconstruction of temperature and precipitation was calculated for the S2 and S3 phases using past ELA and LDPB. During these phases, a depression compared to present of about 4 °C and 1.8 °C of mean annual air temperature was obtained, with correspondent 50% and 23 % reduction of mean annual precipitations. Permafrost today still characterizes the Subboreal rock glaciers and the flow units above 2600 m of the Lateglacial rock glaciers